Pengaruh Brand Ambassador Clarissa Putri terhadap Minat Beli Produk Yellow Fit Kitchen - Ilahi, Vaula Kurnia (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
The purpose of using a brand ambassador is to introduce a new business that is expected to attract the attention of consumers. This study aims to determine and measure the influence of brand ambassadors on buying interest. The theory used in this study is the stimulus response theory. While the method used is a survey method with a quantitative approach. Data was collected by distributing questionnaires to 400 respondents from followers of the Instagram account @clarissaputri_. The data analysis technique used is correlation coefficient test, simple linear regression test, determinant coefficient test and T test and this research was conducted with the positivism paradigm, quantitative approach and explanative survey. In carrying out this testing process, the data is processed using the SPSS version 26 for mac program. In the Pearson correlation, a value of 0.805 was obtained. Based on data collection, it can be stated that the two variables are very strong because they have a determinant coefficient of 64.7%.